Association of upper respiratory tract infection with perioperative respiratory adverse events in pediatric tonsillectomy patients - Shenghua Yu; Cheng Xu; Jun Yao; Jingjie Cai; Rong Wei; Yan Jiang (Italian Journal of Pediatrics)
Abstract Background Upper respiratory tract infections (URTIs) and perioperative respiratory adverse events (PRAEs) pose significant risks for anesthesia in children undergoing tonsillectomy. This study aimed to determine whether URTIs is associated with PRAEs during postanesthesia recovery after tonsillectomy. Methods Children underwent tonsillectomy, with or without adenoidectomy at Shanghai Children’s Hospital from 1 October 2022 to 30 July 2023. We assessed associations between URTIs and PRAEs during postanesthesia recovery in pediatric patients. In total, 94 patients with URTIs were propensity score-matched 1:1 with 94 patients without URTIs. The study’s main outcome measure was the difference in PRAEs incidence between the two groups. Results Children with URTIs were more likely to experience PRAEs than those without URTIs (68 of 94 [72.3%] vs. 25 of 94 [26.6%]; odds ratio [OR], 7.44; 95% CI, 3.34–17.38). They were also more likely to require interventional management post-PRAEs in the post-anesthesia care unit, such as jaw support (OR, 5.01; 95% CI, 2.06–12.20) and mask-assisted oxygenation (OR, 7.85; 95% CI, 3.98–15.50), but no other serious clinical adverse events were observed. Conclusions Children with URTIs had an increased incidence of PRAEs, but only minor interventions were needed to relieve symptoms without serious adverse events. Most children can be safely anesthetized even with URTIs if perioperative anesthesia management is optimized. Trial registration The study protocol was registered with the Chinese Clinical Trial Registry (registration number: ChiCTR2400084682) on 22 May 2024. https://www.chictr.org.cn/showproj.html?proj=230630 .